The Role of the Indonesian Advocates' Code of Ethics in Ensuring Professional Integrity and Legal Justice - Kurniati, Yeti; Suryawin, Paulana Christian; Putra, Erid Gauri; Firdaus, Muhammad Raihan; Haryati, Eti; Gunawan, Ricky; Gunawan, Ryan (Global Education Journal, 2025)
The legal profession in Indonesia plays a crucial role in maintaining justice and upholding the law. Advocates are required to uphold integrity, honesty, and responsibility through adherence to a professional code of ethics. This study aims to analyze the role of the advocate code of ethics in maintaining professional integrity and ensuring legal justice. The research method used is a normative juridical approach, with a literature analysis of various regulations, codes of ethics, and previous research findings. The results indicate that the code of ethics serves as a guideline for behavior, a supervisory instrument, and a means of maintaining public trust in the legal profession. The discussion confirms the positive impact of implementing the code of ethics on public trust, although its implementation still faces obstacles such as a weak Honorary Council, limited enforcement, and fragmentation of advocate organizations. Strengthening efforts are carried out through ethics-based legal education, ongoing development, institutional reform, and public involvement.